2020
DOI: 10.22541/au.160029825.52433360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinal cord compression due to extramedullary hematopoiesis in patient with Beta thalassemia major

Abstract: we reported an18 years old male with beta thalassemia major who presented with back pain progressive over 1 month associated with numbness in thighs, together with lower limbs weakness and difficulty walking. he also mentioned having difficulty in passing urine. he received radiotherapy which results in significant improvement in symptoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In our academic institute, we encountered two patients, in different timelines, with EMH in BTM. Both patients were managed by radiotherapy with excellent outcomes 6,10 . Our experience prompted us to explore the available literature on the management and outcomes of EMH in patients with TDT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our academic institute, we encountered two patients, in different timelines, with EMH in BTM. Both patients were managed by radiotherapy with excellent outcomes 6,10 . Our experience prompted us to explore the available literature on the management and outcomes of EMH in patients with TDT.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the limited retrospective studies and multiple case reports suggests that outcomes in patients managed for EMH in TDT are good. Although there is no agreed‐upon treatment guideline in such patients, various modalities have an excellent response, including conservative management such as blood transfusions and treatments such as radiotherapy and surgical decompression 6 . This systematic review will focus on combining the reported prevalence, demographics, clinical course, management, and outcomes in these patients in an attempt to provide better evidence to formulate clear management guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations